The Role of Spiritual and Religious Experiences in Religious Switching: a Nationwide Study in Brazil - Barros, Maria Cristina Monteiro de (International journal of Latin American religions, 2024)
Religious switching is a key aspect of spirituality that seems to be increasing. Spiritual and religious experiences (SREs) are often reported as inducing religious change; however, there is a shortage of large sample studies investigating this issue. This cross-sectional study aims to explore the associations between SREs and religious switching, highlighting possible clinical implications. Data were collected through a Brazilian nationwide self-administered panel-based online survey, including 1053 participants. Religious switching profile was identified and 16 SREs were tested as predictors of religious switching. Our results show a massive emigration from the dominant Catholic religion towards growing religious affiliations (Neo-Pentecostalism and Spiritism) and secularization. There was a higher proportion of women, mixed race, middle-aged, and married/cohabiting among Converted and a higher proportion of men, young, and single among Secularists. Most SREs were predictors of switching to a new religion. However, the experience of "connection with nature" and "seeing the spirit of a dead person" were also associated to participants who kept their birth religion or to those who became secularists, reflecting the importance of spiritual experiences as phenomena that go across and beyond religion.